Development of Learning Media Based on VideoScribe to Improve Writing Skill for Descriptive Text of English Language Study - Novita Aryuntini; Indri Astuti; Yohanes Gatot Sutapa Yuliana (STKIP Singkawang, 2018)
This study generally aims to develop VideoScribe-based learning media to improve the ability in writing descriptive text in English subjects. The development model used in this study is a combination of Borg and Gall development research steps, and the design of 4D-Thiagarajan learning model includes initial research and information gathering, planning stages, design stages, development stages, revision, and final product stages. The techniques of data collection in this study were carried out through indirect communications and test. Data collection tools used was questionnaires, observation’s sheet, and performance tests. The results showed that the design of instructional media development in this study consisted of (1) The design of the development of learning media was conducted using the modified models Borg and Gall and 4D Thiagarajan. (2) The application of VideoScribe-based learning media through activity as follows a) preparation, b) introduction, d) Evaluation, e) closing. (3) After applying VideoScribe-based learning media to improve students’ ability on writing Descriptive Text in English subjects and conducted pretest and posttest, it can be concluded that there is an increase in students' ability in writing Descriptive Text before and after the use of learning media.